CD8+ T Cells Directed Against a Peptide Epitope Derived From Peptidoglycan-Associated Lipoprotein of Legionella pneumophila Confer Disease Protection - Kim, Sun Jin; Sin, Jeong-Im; Kim, Min Ja (Frontiers in Immunology, 2020)
Legionella pneumophila, an intracellular bacterium, may cause life-threatening pneumonia in immunocompromised individuals. Mononuclear cells and antibodies have been reported to be associated with the host defense response against L. pneumophila. This study is to determine whether Legionella peptidoglycan-associated lipoprotein (PAL)˗specific CD8+ T cells are directly associated with protection against L. pneumophila, with a focus on potential epitopes. Synthetic peptides derived from PAL of L. pneumophila were obtained and tested through in vitro and in vivo cytotoxic T lymphocyte (CTL) assays for immunogenicity. PAL DNA vaccines or a peptide epitope with or without CpG-oligodeoxynucleotides (ODN) was evaluated for protection against L. pneumophila infection in animal models. When mice were immunized with DNA vaccines expressing the PAL of L. pneumophila, they were significantly protected against a lethal challenge with L. pneumophila through induction of antigen-specific CD8+ CTLs. Of the 13 PAL peptides tested, PAL92-100 (EYLKTHPGA) was the most immunogenic and induced the strongest CTL responses. When mice were immunized with the PAL92-100 peptide plus CpG-ODN, they were protected against the lethal challenge, while control mice died within 3–6 days after the challenge. Consistent with lung tissue histological data, bacterial counts in the lungs of immunized mice were significantly lower than those in control mice. Also, the amino acid sequence of PAL92-100 peptides is conserved among various Legionella species. To our knowledge, this study is the first to demonstrate that PAL92-100-specific CD8+ T cells play a central role in the host defense response against L. pneumophila.